Direct α‐Tertiary Alkylations of Ketones in a Combined Copper–Organocatalyst System. Issue 19 (7th April 2021) - Kurose, Ayako; Ishida, Yuto; Hirata, Goki; Nishikata, Takashi
Abstract: Herein, we report an efficient method for the tertiary alkylation of a ketone by using an α‐bromocarbonyl compound as the tertiary alkyl source in a combined Cu‐organocatalyst system. This dual catalyst system enables the addition of a tertiary alkyl radical to an enamine. Mechanistic studies revealed that the catalytically generated enamine is a key intermediate in the catalytic cycle. The developed method can be used to synthesize substituted 1, 4‐dicarbonyl compounds containing quaternary carbons bearing various alkyl chains. Abstract : A copper and pyrrolidine dual catalyst system enables the α‐alkylation of ketones to synthesize 1, 4‐dicarbonyl compounds. The key intermediates are catalytically generated α‐tertiary alkyl radical species and enamines.